2022
DOI: 10.35848/1347-4065/ac51c2
|View full text |Cite
|
Sign up to set email alerts
|

Proton-conductive polymeric ionic liquids block copolymer of poly(vinylphosphonic acid)/1-propylimidazole-b-polystyrene for polymer electrolyte membrane fuel cells

Abstract: Polymer electrolyte membrane fuel cells (PEMFC) have the challenges of operation under low humidity conditions caused by the proton conduction mechanism dependent on water. We focused on polymeric ionic liquids (PIL), which are promising for high proton conductivity under the wide range environment because of having the characteristic of the polymer electrolyte liquid. However, it is difficult to fabricate the self-standing membrane of PIL due to the high hygroscopicity and fluidity. In this paper, to inhibit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Previously, we successfully fabricated polymer electrolyte membranes (PEMs) with high proton conductivity by mixing functionalized nanofillers. Nanoparticle surfaces were precisely coated with polymers that were highly compatible with matrix materials via reversible addition–fragmentation chain transfer (RAFT) polymerization with particles (PwP). Specifically, cellulose nanocrystals (CNCs), known for their high aspect ratio and strength, were used as the core nanoparticles. A copolymer of poly­(vinylphosphonic acid) (PVPA) and polystyrene (PS) (PVPA- b -PS) was used as the shell polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we successfully fabricated polymer electrolyte membranes (PEMs) with high proton conductivity by mixing functionalized nanofillers. Nanoparticle surfaces were precisely coated with polymers that were highly compatible with matrix materials via reversible addition–fragmentation chain transfer (RAFT) polymerization with particles (PwP). Specifically, cellulose nanocrystals (CNCs), known for their high aspect ratio and strength, were used as the core nanoparticles. A copolymer of poly­(vinylphosphonic acid) (PVPA) and polystyrene (PS) (PVPA- b -PS) was used as the shell polymer.…”
Section: Introductionmentioning
confidence: 99%
“…The original decomposition temperature of Im was 150 to 200 °C, suggesting here that the formation of ionic liquids with PVPA enhanced the heat resistance. [ 53 ] Based on previous studies, it has been found that PAA decomposes at 500 °C, while PS shows a rapid weight loss at 300 to 400 °C. [ 54 ] Silica@PVPA/Im/PAA‐ b ‐PS have indicated a weight loss corresponding to PAA and PS from 200 to 500 °C.…”
Section: Resultsmentioning
confidence: 99%
“…These results compared to our previous study, the proton conductivity of block copolymer of PILs and polystyrene (PILs-b-PS) was 1.6 × 10 −4 S cm −1 (80 °C, 80% RH) and 4.5 × 10 −5 S cm −1 (80 °C, 70% RH), respectively. 19) In contrast, silica@PILs-10X 1 was 5.0 × 10 −3 S cm −1 (80 °C, 80% RH) and 6.9 × 10 −4 S cm −1 (80 °C, 70% RH), respectively. Surprisingly, even similar types of PILs succeeded in improving proton conductivity depending on the sample states.…”
Section: Sample Namementioning
confidence: 90%
“…17,18) According to these facts, although the ILs exhibited high proton conductivity in low-humidity environments, their fluidity due to lower melting point was a concern for leaching from PEM. [19][20][21] In order to suppress their fluidity, some approaches have been reported that cross-linking with ILs each other and mixing them into polymer matrixes. [22][23][24][25][26][27][28] However, these methods decrease the proton conductivity of PEM.…”
Section: Introductionmentioning
confidence: 99%